Kelayakan Pengembangan Agrowisata pada Beberapa Kecamatan di Kabupaten Pelalawan - Febrianti, Nur; Fredesman, Muhammad (JURNAL RISET INOVASI DAERAH, 2024)
This study aims to identify and evaluate the feasibility of developing agrotourism in Langgam, Teluk Meranti, and Kuala Kampar Subdistricts, Pelalawan Regency, Riau Province. With significant land area and diversity of agricultural commodities, as well as the potential for Malay culture-based agrotourism, these three subdistricts show great potential for development. The research methods involved collecting primary and secondary data through observation, interviews, and documentation, using a descriptive approach to analyze land suitability, demographics, productive enterprises, infrastructure, and accessibility. The results indicate that Langgam Subdistrict has a higher feasibility level for agrotourism development compared to Teluk Meranti and Kuala Kampar, supported by diverse productive enterprises, good accessibility, and readiness of human resources. The main challenge is the low regional original income, which affects investment capacity. Teluk Meranti and Kuala Kampar require capacity building for human resources, improvement in accessibility, and diversification of productive enterprises to enhance their agrotourism potential. A comprehensive and collaborative development strategy between the government, community, and private sector is essential to address challenges and maximize agrotourism potential, which not only provides economic benefits but also social and environmental benefits for the local community, ensuring long-term sustainability and improving community welfare.